2019
DOI: 10.1155/2019/5869206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, Treatment, Control, and the Associated Factors of Diabetes in an Iranian Kurdish Population

Abstract: Aims. This study is aimed at estimating the prevalence, awareness, treatment, and glycemic control of diabetes mellitus (DM) and its associated factors in an Iranian Kurdish population. Methods. Baseline data of the Ravansar Non-communicable Disease (RaNCD) cohort study, consisting of adults aged 35-65 years, were used. Diabetes was defined as a fasting plasma glucose (FPG) of 126 mg/dl or higher, being on diabetes medication, and/or diabetes confirmed by a health practitioner. Results. Nine thousand nine hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
6
18
2
Order By: Relevance
“…Prevalence of diabetes in the present study was identical to a survey conducted by Yazdanpanah et al in 2015, which is the only available report on diabetes from southwestern Iran (15.2% vs. 15.1%) (17) and comparable to two recent studies from central (16.1%) (18) and Northern Iran (17.2%) (7). However, this prevalence was nearly two-fold higher compared to the national estimations (19) and other parts of the country, including western (20), southeastern (21), and southern areas (22). Besides, the prevalence of self-reported diabetes was comparable to the national estimations (8.9 vs. 10%) (23).…”
Section: Discussionsupporting
confidence: 88%
“…Prevalence of diabetes in the present study was identical to a survey conducted by Yazdanpanah et al in 2015, which is the only available report on diabetes from southwestern Iran (15.2% vs. 15.1%) (17) and comparable to two recent studies from central (16.1%) (18) and Northern Iran (17.2%) (7). However, this prevalence was nearly two-fold higher compared to the national estimations (19) and other parts of the country, including western (20), southeastern (21), and southern areas (22). Besides, the prevalence of self-reported diabetes was comparable to the national estimations (8.9 vs. 10%) (23).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of diabetes in this study was identical to a survey conducted by Yazdanpanah et al in 2015, which is the only available report on diabetes from southwestern Iran (15.3% vs. 15.1%) [ 24 ], and was comparable to two recent studies from central (16.1%) [ 25 ] and Northern Iran (17.2%) [ 9 ]. However, this prevalence was nearly two-fold higher compared to the national estimations [ 26 ] and other parts of the country, including western [ 27 ], southeastern [ 28 ], and southern areas [ 29 ]. For prediabetes, two population-based studies in central and southeastern Iran have reported a lower prevalence (26 and 19%); however, in both studies, individuals under the age of 35 years were also recruited [ 25 ].…”
Section: Discussionmentioning
confidence: 88%
“…It is well established in the literature that exercise is an important protective factor for diabetes ( Esteghamati et al, 2014 ; Li et al, 2015 ; Roya et al, 2019 ). There is a direct beneficial effect of exercise on β cell function ( Li et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%